Preformulation design of PLGA particulate system for multi-day drug delivery of the antidepressant mirtazapine - Holická, Martina; Muselík, Jan; Kejdušová, Martina; Pavelková, Miroslava; Kubová, Kateřina; Doležel, Petr; Vetchý, David; Košťál, Vratislav; Vysloužil, Jakub; Mašek, Josef (Ceska a Slovenska farmacie, 2021)
In this experimental study, the biodegradable polylactide-co-glycolide (PLGA) microparticles (MP) loaded with the insoluble antidepressant mirtazapine were prepared by the simple o/w solvent evaporation method. The formation involved intrinsic variables, such as the content of polymer (700, 900 or 1200 mg), dichloromethane (5 or 10 ml) and/or drug (200 or 400 or 600 mg), and the volume of the aqueous emulsion phase (400, 600 or 800 ml). The influence of these parameters on the size and morphology of microparticles, encapsulation efficiency, and drug release behavior was observed. All MP were successfully prepared, and their size ranged between 165.34 ± 42.88 and 360.17 ± 121.59 μm. MP exhibited prolonged drug release (days), and some profiles had multiphasic character. It was found that the samples prepared with a higher initial amount of PLGA were bigger with prolonged lag time up to 34.3 hours. On the other hand, higher drug concentrations reduced the lag time. The external phase volume reduction and multiplication of dichloromethane amount prolonged the mirtazapine release and decreased the encapsulation efficiency. These observations were further confirmed by multivariate data analysis.
Keywords: solvent evaporation method; PLGA; mirtazapine; Particle Size; Antidepressive Agents; Polyglycolic Acid; kopolymer kyseliny glykolové a mléčné; Polylactic Acid-Polyglycolic Acid Copolymer; kyselina polyglykolová; microparticles; multivariate data analysis; Microspheres; Lactic Acid; mirtazapin; antidepresiva; velikost částic; mikrosféry; Mirtazapine; kyselina mléčná